Chromosome Partitioning in Escherichia coli in the Absence of Dam-Directed Methylation - Vinella, Daniel (1992)
Escherichia coli dam mutants, lacking the GATC DNA methylase, do not produce anucleate cells at high frequencies, suggesting that hemimethylation of the chromosome origin of replication, oriC, is not essential for correct chromosome partitioning.